Violante de Albión, Aragonese Camarera of Isabel of Castile. Chamber Management, Circulation of Goods, and Material Culture in an Itinerant Court (1499–1505) (Edad Media. Revista de Historia, 2026)
This article explores the figure of Violante de Albión, an Aragonese lady who managed part of the goods of Queen Isabel of Castile’s chamber. It examines Violante’s genealogy and family trajectory, her management of the inflow and outflow of luxury objects at court, and her role in the auction of the chamber’s possessions after the queen’s death. The study is based on a comprehensive analysis of a record from the Contaduría Mayor de Cuentas of Castile, preserved in the Archivo General de Simancas, which contains 457 entries referring to the lady.
Keywords: court; chamber; female agency; material culture; Isabella of Castile